1998
DOI: 10.1128/iai.66.10.4690-4695.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Cysteine-Cysteine Family of Chemokines RANTES, MIP-1α, and MIP-1β Induce Trypanocidal Activity in Human Macrophages via Nitric Oxide

Abstract: This paper describes a new role for the cysteine-cysteine (CC) chemokines RANTES, MIP-1α, and MIP-1β on human macrophage function, which is the induction of nitric oxide (NO)-mediated trypanocidal activity. In a previous report, we showed that RANTES, MIP-1α and MIP-1β enhance Trypanosoma cruzi uptake and promote parasite killing by human macrophages (M. F. Lima, Y. Zhang, and F. Villalta, Cell. Mol. Biol. 43:1067–1076, 1997). Here we study the mechanism by which RANTES, MIP-1α, and MIP-1β activate human macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0
3

Year Published

1999
1999
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(45 citation statements)
references
References 52 publications
0
42
0
3
Order By: Relevance
“…It is now clear that IFN-g-and TNF-a-activated macrophages control of the replication of T. cruzi in various hosts [20]. The mechanism by which macrophages are able to kill intracellular parasites has been shown to be dependent on NO [8][9][10][11][12][13]20], although a recent study using T. cruzi strains Tulahuen and Brazil suggested that inducible NO synthase (iNOS) is not required to control parasite replication in vivo [21]. However, much less is known about the mechanisms governing the migration of leukocytes to sites of tissue infection, especially to hearts of infected hosts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is now clear that IFN-g-and TNF-a-activated macrophages control of the replication of T. cruzi in various hosts [20]. The mechanism by which macrophages are able to kill intracellular parasites has been shown to be dependent on NO [8][9][10][11][12][13]20], although a recent study using T. cruzi strains Tulahuen and Brazil suggested that inducible NO synthase (iNOS) is not required to control parasite replication in vivo [21]. However, much less is known about the mechanisms governing the migration of leukocytes to sites of tissue infection, especially to hearts of infected hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Infection of macrophages [9] and cardiomyocytes [10] with T. cruzi trypomastigote forms is accompanied by the significant production of several chemokines, including CCL3, CCL4, and CCL5. Not only can the latter cells produce chemokines, but chemokines can also act on the cells to induce iNOS expression, NO expression, and the killing of parasites [9][10][11][12][13]. Thus, in the present study, it was important to ascertain whether chemokine expression would also occur in vivo after infection of mice with the Y strain of T. cruzi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MbO 2 (Fe(II)O 2 ) reacts rapidly with NO to yield nitrate (NO 3 3 ) and metMb (Fe(III)) [20]. Moreover, de-oxyMb (Fe(II)) binds NO yielding MbNO (Fe(II)NO) which in the presence of O 2 may be converted to metMb (Fe(III)) and NO 3 3 [23]. These reactions quench free NO, which may inactivate cysteine-containing and metallo-enzymes [2,16,24].…”
mentioning
confidence: 99%
“…NO detoxi¢cation facilitated by Mb may thus protect T. cruzi colonizing the cardiomyocytes from the adverse e¡ects of NO. NO may bind also to metMb (Fe(III)) yielding metMbNO (Fe(III)NO), which in the presence of metMb reductase and O 2 may be converted to metMb (Fe(III)) and NO 3 3 . However, this process does not appear of physiological relevance, being thermodynamically and kinetically unfavorable [19,232 5].…”
mentioning
confidence: 99%